(untitled) (Journal of history-rus, 2023)
The article is devoted to the analysis of modern historiography on the problem of the process of co-optation of the local population into the system of administrative governance in the national regions of the Russian Empire (Kazakhstan, Siberia, Poland and Ukraine) through the study of monographic studies and research papers by scholars from various regions. The article uses a comparative method that allowed us to show the tools and mechanisms used by the imperial authorities in the process of integrating the local population into the empire and how Russian officials implemented new governance models in the national regions. In modern Kazakhstan historiography attention is focused on the formation of a corps of officials, methods of attracting local nobility to the service to the empire. In modern Russian historiography on the problem of governance in Siberia, works on the history of governance, the formation of officialdom and the incorporation of local nobility into the imperial system of governance are highlighted. Modern Polish researchers in their works explore the service, activities of Polish officials and their political career in the system of imperial power structures. In the modern historiography of Ukraine, issues on the negative consequences of imperial administrative reforms, the specifics of an implementation of the imperial governance model and the loyalty of the local nobility to these innovations are highlighted. In addition, the article reflects the main problems that require further study and application of new scientific methods, including interdisciplinary approaches. Keywords: historiography, incorporation, officials, bureaucracy, empire, regions, local government, imperial governance model.